Artificial intelligence-rationalized balanced PPARα/γ dual agonism resets dysregulated macrophage processes in inflammatory bowel disease - Gajanan D. Katkar; Ibrahim M. Sayed; Mahitha Shree Anandachar; Vanessa Castillo; Eleadah Vidales; Daniel Toobian; Fatima Usmani; Joseph R. Sawires; Geoffray Leriche; Jerry Yang; William J. Sandborn; Soumita Das; et al. (Communications Biology, 2022)
A Boolean network explorer (BoNE) computational algorithm was used to identify a dual agonist of the nuclear receptors PPARα and PPARγ that may be therapeutic in treating inflammatory bowel disease.